Consumption of ultra-processed foods and risk for Alzheimer’s disease: a systematic review - Claudino, Paola Alves; Bueno, Nassib Bezerra; Piloneto, Sabrina; Halaiko, Dieniffer; Azevedo de Sousa, Leticia Priscila; Barroso Jara Maia, Cassia Helena; Netto, Bárbara Dal Molin (Frontiers in Nutrition, 2024)
To investigate the association of the consumption of ultra-processed foods with the risk of developing Alzheimer's disease in adults and the elderly. The review protocol was registered on PROSPERO (CRD42022375944). Methods: This is a systematic review reported according to PRISMA guidelines. Observational studies were included without language or publication year restrictions. Studies assessing only other types of dementia as outcomes, not considering Alzheimer's disease, were excluded. The research was carried out in the Medline, Embase, Lilacs databases, and a survey of the gray literature between April and November 2023, in addition to citation search in the included studies. Data extraction was performed by two independent reviewers. The risk of bias and methodological quality of the included studies were assessed using the Joanna Briggs Institute checklist for cohort studies. Results: A total of 5 studies involving 617,502 adults and elderly people were included. All studies had a cohort design and were considered of high methodological quality. Of the included studies, 4 demonstrated a risk association between the consumption of ultra-processed foods and the development of Alzheimer's disease, while 1 study showed a risk association only with the development of cognitive decline. Discussion: The association between ultra-processed foods consumption and the risk of developing Alzheimer's disease is a recent topic in scientific studies, given that the oldest study identified by our review dates back to 2017. Of the four included studies, three showed a significant association between ultra-processed foods consumption and the risk of developing Alzheimer's disease.